Tolerability of PSMA radioligand therapy in metastatic prostate cancer patients with baseline mild to moderate leukopenia - Moritz B. Bastian; Tilman Speicher; Arne Blickle; Caroline Burgard; Julius L. D. Bastian; Mark Bartholomä; Andrea Schaefer-Schuler; Stephan Maus; Samer Ezziddin; Florian Rosar (EJNMMI Research)
Abstract Background Aim of this study was to analyze the safety of prostate-specific membrane antigen radioligand therapy (PSMA-RLT) in patients with metastatic castration-resistant prostate cancer (mCRPC) with preexisting mild to moderate leukopenia (CTCAE ≥ 1). Results Thirty-seven mCRPC patients with preexisting leukopenia (leukocyte count < 3.8 × 109/L) were included in this study. Patients received a median of 3 cycles of [177Lu]Lu-PSMA-617 (range 1–9). No significant difference in leukocyte counts was observed between baseline and follow-up after each PSMA-RLT cycle: first cycle (3.0 ± 0.5 at baseline vs. 3.4 ± 1.4 at follow up [in × 109/L], p = 0.0921), second cycle (3.1 ± 0.4 vs. 3.8 ± 1.7, p = 0. 0.0509), and third cycle (3.1 ± 0.4 vs. 3.2 ± 2.0, p = 0.2929), respectively. Similarly, baseline and end of treatment values, irrespective of the number of administered cycles, did not reveal a significant difference (3.0 ± 0.5 vs. 3.5 ± 1.4, p = 0.0684). After the end of therapy, irrespective of the number of administered cycles, 27% patients remained stable in terms of CTCAE scoring, 46% changed to a higher score and 27% improved to a lower score. Conclusion Although marked preexisting leukopenia is often considered a relative contraindication for PSMA-RLT, our findings indicate that PSMA-RLT is feasible in patients with leukopenia of CTCAE grade ≥ 1. In our cohort, leukocyte counts remained stable without significant RLT-induced deterioration. Therefore, patients with leukopenia should not be categorically excluded from receiving PSMA-RLT. Trial registration: Clinicaltrials.gov identifier: NCT04833517, registered 01.01.2016.